2007
DOI: 10.1016/j.jsat.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Are Washington Circle performance measures associated with decreased criminal activity following treatment?

Abstract: This study examines the association between adherence to during-treatment process measures of quality (defined as initiation and engagement in treatment as developed by the Washington Circle) and outcome measures (defined as arrests and incarcerations) in the following year. The data come from the Oklahoma Department of Mental Health and Substance Abuse Services (ODMHSAS) administrative data system linked to data from state agencies involved in criminal justice. Clients who initiated a new episode of outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 35 publications
5
59
1
Order By: Relevance
“…Among client characteristics, being younger than 45 years of age, having a high school education or more, and being employed at baseline predicted a higher probability of being employed in the year after treatment index. Also, clients who began substance use in the age ranges of (11)(12)(13)(14), (15)(16)(17) and (18)(19)(20) were more likely to be employed than those reporting first use at 21 and older. On the other hand, clients who reported opiate use in the last 30 days and clients with a treatment index occurring during the fourth quarter in 2008 were significantly less likely to be employed in the year following their index.…”
Section: Multivariate Results For Other Client and Facility Charactermentioning
confidence: 98%
See 2 more Smart Citations
“…Among client characteristics, being younger than 45 years of age, having a high school education or more, and being employed at baseline predicted a higher probability of being employed in the year after treatment index. Also, clients who began substance use in the age ranges of (11)(12)(13)(14), (15)(16)(17) and (18)(19)(20) were more likely to be employed than those reporting first use at 21 and older. On the other hand, clients who reported opiate use in the last 30 days and clients with a treatment index occurring during the fourth quarter in 2008 were significantly less likely to be employed in the year following their index.…”
Section: Multivariate Results For Other Client and Facility Charactermentioning
confidence: 98%
“…This study adds to the evidence supporting the association between a process-focused measure of performance for the treatment of substance use disorders and outcomes. 14,31,32 Finally, through collaboration across sectors and the merging of data from multiple agencies such as across substance abuse treatment, employment, and criminal justice agencies, this research has shown how performance measures in one sector can be associated with outcomes in another. One critical next step is for policy makers and treatment providers both in Washington State and other states to consider how to improve on engaging clients in outpatient care through providing feedback to providers, internal quality improvement efforts (e.g., implementing financial incentives), and continuing efforts to collaborate across agencies.…”
Section: Implications For Behavioral Healthmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, thus far addiction treatment initiatives have focused heavily on access to treatment, utilization of treatment and retention in treatment. [7,9] The metrics used here included patient engagement in treatment services and aftercare activities as well as patient perception of the quality of care and helpfulness of care, and to some extent, the cost of care (as captured in the residential treatment readmission metric).…”
Section: Logistical Challenges In Implementing P4p Metrics For Addictmentioning
confidence: 99%
“…Patients who initiated an outpatient substance abuse treatment episode and remained engaged in treatment were significantly less likely to be arrested or incarcerated in the year following treatment. [9] A study examining adolescents attending substance use disorder treatment services found that those who regularly engaged in outpatient services were less likely than unengaged patients to use drugs or alcohol during a 6 month follow up. However, treatment engagement was unrelated to criminal behavior at follow up.…”
Section: Introductionmentioning
confidence: 99%